1971
DOI: 10.1126/science.172.3982.475
|View full text |Cite
|
Sign up to set email alerts
|

Cholestasis: Lamellar Structure of the Abnormal Human Serum Lipoprotein

Abstract: An abnormal lipoprotein was visualized directly in serum by electron microscopy of preparations negatively stained with potassium phosphotungstate. It appears as a unique disk-shaped particle with major axis measuring 400 to 600 angstroms and minor axis measuring about 100 angstroms. Chemical analysis, viscosity measurements, and x-ray diffraction analysis of purified preparations indicate that the particle, consisting of a one-to-one molar mixture of cholesterol and choline phosphatides associated with a smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
1

Year Published

1972
1972
1998
1998

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(62 citation statements)
references
References 22 publications
5
56
0
1
Order By: Relevance
“…2B) suggested that the VLDL/IDL fractions might contain lipoproteins consisting of apoB-free lamellar-free cholesterol/phospholipid particles, i.e. lipoprotein X-like particles of vesicular structure (24). Subsequently, SR-BI Tg mice were found to have functional LCAT deficiency (see below) in which lipoprotein X accumulates especially on a high fat diet (25,26).…”
Section: Sr-bi Expression In Sr-bi Tgmentioning
confidence: 99%
“…2B) suggested that the VLDL/IDL fractions might contain lipoproteins consisting of apoB-free lamellar-free cholesterol/phospholipid particles, i.e. lipoprotein X-like particles of vesicular structure (24). Subsequently, SR-BI Tg mice were found to have functional LCAT deficiency (see below) in which lipoprotein X accumulates especially on a high fat diet (25,26).…”
Section: Sr-bi Expression In Sr-bi Tgmentioning
confidence: 99%
“…Agarose gel electrophoresis of lipoproteins in plasma and lipoprotein fractions was performed as described. 17 The distribution of particle diameters of negatively stained lipoproteins 20 was estimated from photographic prints at a magnification of 180,000 by a semiautomated method, utilizing a magnetic digitizer. Three points were marked on the circumference of each of 100 particles and the diameters were calculated by computer, programmed for a threepoint geometric algorithm.…”
Section: Analysesmentioning
confidence: 99%
“…28 Electron microscopy of lipoprotein fractions was performed on samples negatively stained with potassium phosphotungstate. 29 Particle diameters were measured on the photographic negative plates with a Nikon optical microcomparator (Model 6 C, Nippon Kogaku, KK, Tokyo, Japan). Apo B-48 antigen was identified by double immunodiffusion 30 against a rabbit antiserum specific for the apo B-48 lipoprotein.…”
Section: Lipoprotein Analysesmentioning
confidence: 99%